Impactos econômicos da nova realidade da exploração do pré-sal. Existe uma ameaça ao etanol? - Bistafa, Rafael Campos (2016)
From the mid-2000s onwards, the Brazilian ethanol production returned to thrive. In the meantime, in 2007 the discovery of large reserves of oil in the pre-salt layer in the Brazilian coastline was announced. Thus, the promising outlook for the Brazilian ethanol industry began to give way to the development of pre-salt oil with an ambitious investment program. Beyond that, between 2011 and 2014 the Government adopted a new domestic pricing policy for gasoline and diesel, aiming to reduce inflationary pressures, but gradually reducing ethanol competitiveness, besides imposing a high commitment of Petrobras' financial situation, hampering investment in the pre-salt itself. Considering such challenges and the importance of the oil and ethanol sectors to the Brazilian economy, this study aims to evaluate the long run economic impacts of the pre-salt oil production, with special attention to the consequences to the ethanol sector. An evaluation of the 2011-2014 gasoline price control policy impacts on the ethanol sector is realized. An adapted recursive dynamic general equilibrium model is employed in which the pre-salt oil sector is added as a backstop technology. The results suggest that premature stimulus of pre-salt production to achieve the Government’s expected oil production brings more costs than benefits to the Brazilian economy. It was found that without Government interference, the pre-salt oil production would be competitive only after 2025-2035. With respect to the impact on the ethanol industry, it was found that the pre-salt development does not impair the Brazilian ethanol production. Nonetheless, the gasoline price control policy had a negative impact on the ethanol sector.